Short-period evolution in EU legal texts - Peruzzo, Katia (Linguistica (Ljubljana), 2013)
Due to the ever-changing legal landscape of the European Union, the terminology used in EU documents is subject to constant formal and conceptual evolution. In this paper, a bilingual (Italian and English) corpus of equally authentic EU legal texts covering a time span of fifteen years (1998-2012) and concerning the legal area of victims of crime is analysed from a diachronic perspective. The aim is to discuss the terminological changes observed in the corpus in the light of the classification of evolution phenomena proposed by Tartier (2003) and Picton (2011). In order to examine both formal and conceptual terminological evolution, the distinction between genotypes and phenotypes introduced by Sacco (1991) is applied to the terms identified in the corpus and the underlying concepts. The analysis of the EU corpus shows that the three categories proposed by Tartier (appearance, disappearance and stability) and the first three (novelty and obsolescence, implantation of terms and concepts, and centrality) of the four categories proposed by Picton for the terminology of space technologies also apply to the terms of the examined legal area.
Keywords: 1998/2012; diachronie; diahronija; European Union; Evropska unija; law; pravna terminologija; pravo; terminologie; terminologie juridique; terminologija; terminology; textes juridiques; Union européenne